Application of a new protocol for providing obstetric care in an outpatient service during the COVID-19 pandemic in a public hospital in Madrid, Spain - Rayo, Maria N.; Fernández-Buhigas, Irene; Ferrer, Emilia; Arrébola, María; Gil, María M.; Santacruz, Belén (Frontiers in Medicine, 2022)
Objective: To evaluate the clinical implementation of a preventive Covid-19 protocol regarding re-organization of appointments and documented infections among health workers in an obstetric outpatient service. Methods: Descriptive analysis of the antenatal care at our obstetric outpatient service and infection rates among health care providers from March 19th to May 22nd, 2020. Appointments were divided into telephone calls or face-to-face examinations. A pre-consultation triage was implemented to identify suspected SARS-CoV2 infected women to reschedule them 14 days later or, if the consultation was non-delayable, to use complete Personal Protective Equipment (PPE). Firstly, the number of face-to-face appointments, telephone appointments, and Covid-19 diagnoses in pregnant women were analyzed. Secondly, the number of obstetricians and nurses diagnosed with SARS-CoV2 infection and their serologic status during universal screening in May 2020 were recorded. Results: 1842 obstetric appointments were scheduled during this period, including 432 (23.5%) telephone appointments (96.53% according to clinical protocol, 1.62% symptomatic patients advised to stay at home, and 1.85% Covid-19 confirmed cases), and 1410 (76.5%) face-to-face appointments (9.7% did not attend due to fear of getting the infection, 3.1% were lost-to-follow-up, 0.5% were rescheduled due to Covid-19 symptoms and 86.7% who did attend). Of the 1223 women attending their hospital appointment, 3.6% screened positive at the triage (72.7% rescheduled and 27.3% seen with PPE). 43 rRT-PCR-SARS-CoV2 tests were performed, and two tested positive. No Covid-19 symptoms were reported among health workers at the outpatient obstetric service, and only one nurse presented immunoglobulin (Ig)G anti-SARS-CoV2. Conclusion: A prompt implementation of a preventive protocol in a hospital obstetric outpatient service, including triage, hygienic and preventive measurements, and rescheduling pregnancy appointments, reduces the percentage of health workers affected by SARS-CoV2.